2022
DOI: 10.3390/antiox11122480
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Metabolome Analysis of a Late-Senescent Vegetable Soybean during Seed Development Provides New Insights into Degradation of Chlorophyll

Abstract: (1) Background: Senescence represents the final stage of plant growth and development, which transfers nutrients to growing seeds and directly affects the yield and quality of crops. However, little is known about chlorophyll degradation in developing and maturing seeds, in contrast to leaf senescence; (2) Methods: RNA-Seq was used to analyze the differentially expressed genes of different late-senescent germplasms. A widely untargeted metabolic analysis was used to analyze differential metabolites. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…Plastochromanol-8 (PC-8), an efficient scavenger of 1 O 2 , efficiently safeguards lipids against photooxidative damage in Arabidopsis plants (Szymańska and Kruk 2010 ; Rastogi et al 2014 ). Metabolomics research has further demonstrated that three flavonoid metabolites exclusively found in late-maturing soybean seeds (farrerol-7- O -glucoside, cyanidin-3- o -(6′- o -feruloyl) glucoside, and kaempferide-3- o -(6′-malonyl) glucoside) can effectively mitigate Chl degradation by scavenging oxygen free radicals within the chloroplasts (Wang et al 2022a ). However, there is still a need to explore additional mechanisms involved in maintaining equilibrium between Chl and ROS.…”
Section: Imbalance Of Chlorophyll Metabolism and The Presence Of Anti...mentioning
confidence: 99%
“…Plastochromanol-8 (PC-8), an efficient scavenger of 1 O 2 , efficiently safeguards lipids against photooxidative damage in Arabidopsis plants (Szymańska and Kruk 2010 ; Rastogi et al 2014 ). Metabolomics research has further demonstrated that three flavonoid metabolites exclusively found in late-maturing soybean seeds (farrerol-7- O -glucoside, cyanidin-3- o -(6′- o -feruloyl) glucoside, and kaempferide-3- o -(6′-malonyl) glucoside) can effectively mitigate Chl degradation by scavenging oxygen free radicals within the chloroplasts (Wang et al 2022a ). However, there is still a need to explore additional mechanisms involved in maintaining equilibrium between Chl and ROS.…”
Section: Imbalance Of Chlorophyll Metabolism and The Presence Of Anti...mentioning
confidence: 99%
“…Different hormones have specific functions in activating/inhibiting and controlling leaf senescence, and photosynthesis [10], hormone transduction [11], MAPK signaling [12], and carbon fixation by photosynthetic organisms all play important regulatory roles in leaf growth and development [13,14]. Different canopy leaves of crops are subjected to different light intensities, resulting in changes in leaf photosynthesis [15] that have a great impact on the subsequent physiological characteristics of leaves in terms of photochemical energy, photosynthesis, and carbon assimilation [16]. One of the most striking features of leaf senescence is the decline in photosynthetic capacity.…”
Section: Introductionmentioning
confidence: 99%